The psychology of learning and motivation : advances in research and theory. - Medin, Douglas L. (Psychology of learning and motivation, 1993)
The Psychology of Learning and Motivation publishes empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditions to complex learning and problem solving. This guest-edited special volume is devoted to current research and discussion on associative versus cognitive accounts of learning. Written by major investigators in the field, topics include all aspects of causal learning in an open forum in which different approaches are brought together. Key Features * Up-to-date review of the literature * Discusses recent controversies * Presents major advances in understanding causal learning * Synthesizes contrasting approaches * Includes important empirical contributions * Written by leading researchers in the field.